PEMBUATAN INDEKS ARTIKEL SURAT KABAR BERSUBJEK COVID-19 DI DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI SUMATERA BARAT - Irna, Irna; Fitri, Mega Orina; Rahmi, Lailatur; Doni, Sefri (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2021)
This research is motivated by the problem of the absence of a search tool in the archives and library services of the province of West Sumatra that can make it easier for users to search for information about Corona Virus Disease (Covid-19) articles correctly, the purpose of this study is to create an index as a valid, practical search tool. and effective, so that it can make it easier for users to browse information about Covid-19 articles. This type of research is development research, namely research that is used to produce certain products and can be tested for the effectiveness of these products. The stages that are passed in product development are needs analysis, product design, product development and product evaluation or testing. The results of the study were in the form of an index of newspaper articles with the subject of Covid-19 at the Archives and Library Service of West Sumatra Province. The resulting product is validated by expert validators and tested on a limited basis through individual and group trials. The test results prove that the resulting product is valid because it has been proven with an A value of 96%, effective because it has been tested with a value of 86% and practically proven by a value of 92%. The results of the questionnaire prove that the index of newspaper articles with the subject of Covid-19 can be used and makes it easier for users to search for information about Covid-19 articles. Keywords: Indeks,Coronavirus Disease, Covid-19, Surat Kabar, Temu Kembali Informasi, Perpustakaan Umum